Pemertahanan Budaya Alat Musik Gamolan Melalui Penciptaan Lagu Gamolan Sakti - Riki Rahmat Dinata; Indar Sabri; Welly Suryandoko; Trisakti Trisakti; Retnayu Prasetyanti Sekti (Universitas Hamzanwadi, 2025)
Gamolan is a musical instrument made of bamboo that is played by beating so that it produces tones. The tones are distinguished by notes or scales. Gamolan comes from the word begamol, the word begamol in Lampung language is the same as the word begumul in Malay language which means gathering. The research “Cultural Preservation of Gamolan Musical Instruments through the Creation of Gamolan Sakti Songs” aims to explore how traditional songs can be used as a tool to preserve and promote the cultural heritage of Gamolan musical instruments in Lampung. The song created by Hasyim Kan combines traditional elements with modern musical innovations. This research uses a qualitative descriptive method. This research uses the theory of Anthropology from Koentjaraningrat with the Culture Knowlade approach and is conducted at the University of Lampung and Hasyim Kan as the main source. The main sources are observation of the process of playing Gamolan musical instruments, learning Gamolan Sakti songs performed by Hasyim Kan, literature studies in libraries, books, national journals and other literature. The results showed that the Gamolan Sakti song has had a positive impact on the youth community in Lampung, especially in strengthening their cultural identity as Lampung people and increasing their pride in local cultural heritage. The song has helped the younger generation develop interest and experience in playing Gamolan musical instruments, as well as raising awareness and appreciation of Gamolan culture in Lampung. Despite the challenges in preserving Gamolan music culture, “Gamolan Sakti” has successfully overcome these challenges and made an impact on the youth community in Lampung. This researcher hopes that the Gamolan musical instrument from Lampung will not be lost in the modern era and will continue to be appreciated and loved by future generations.